A novel inverter control strategy for maximum hosting capacity photovoltaic systems in distribution networks using power factor. - Ahmed Alfouly; Mohamed A Ismeil; I Hamdan (PLoS ONE)
The conventional inverter is undergoing a transformation into a smart inverter, driven by the expanding penetration of Photovoltaic (PV) power production in Low Voltage (LV) systems. The adoption of smart inverters is on the rise. Power companies are keen on integrating them into their networks to acquire essential frequency and voltage support as required. These inverters actively exchange actual and reactive power in connection with the grid, altering the system's operational state. This dynamic behavior within the distribution level of power networks might give rise to unprecedented issues. This paper investigates the influence of diverse connection prerequisites that explore the methods for determining the Hosting Capacity (HC) of PV solar systems and their applicability within the low-voltage utility grid. Smart inverters provided with different Volt-VAr and Power Factor (PF) regulation capabilities are analyzed using MATLAB SIMULINK. The outcomes reveal a notable augmentation in the network's HC. This progress improves the grid's attributes, and the incorporation of smart inverter functionalities stands to considerably facilitate incorporating PV solar installations into electrical networks.